Experimental and numerical investigation of the effective electrical conductivity of nitrogen-doped graphene nanofluids - Mehrali, M.; Sadeghinezhad, E.; Rashidi, M.M.; Akhiani, A.R.; Latibari, S.T.; Mehrali, M.; Metselaar, H.S.C. (Springer Verlag, 2015)
Electrical conductivity is an important property for technological applications of nanofluids that have not been widely investigated, and few studies have been concerned about the electrical conductivity. In this study, nitrogen-doped graphene (NDG) nanofluids were prepared using the two-step method in an aqueous solution of 0.025 wt Triton X-100 as a surfactant at several concentrations (0.01, 0.02, 0.04, 0.06 wt). The electrical conductivity of the aqueous NDG nanofluids showed a linear dependence on the concentration and increased up to 1814.96 for a loading of 0.06 wt NDG nanosheet. From the experimental data, empirical models were developed to express the electrical conductivity as functions of temperature and concentration. It was observed that increasing the temperature has much greater effect on electrical conductivity enhancement than increasing the NDG nanosheet loading. Additionally, by considering the electrophoresis of the NDG nanosheets, a straightforward electrical conductivity model is established to modulate and understand the experimental results.